2011
DOI: 10.4319/lo.2012.57.1.0124
|View full text |Cite
|
Sign up to set email alerts
|

In situ variability of mass‐specific beam attenuation and backscattering of marine particles with respect to particle size, density, and composition

Abstract: This study analyzes relationships between concentration of suspended particles represented by dry mass, [SPM], or area, [AC], and optical properties including particulate beam attenuation (c p ), side scattering (b s ), and backscattering (b bp ), obtained from an intensive sampling program in coastal and offshore waters around Europe and French Guyana. First-order optical properties are driven by particle concentration with best predictions of [SPM] by b bp and b s , and of [AC] by c p . Second-order variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
179
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(212 citation statements)
references
References 82 publications
16
179
3
Order By: Relevance
“…The variability in mass specific optical properties, when compared across studies, has been found to be constrained within ±50% despite some variability in the analytical methods used to obtain mass (Boss et al, 2009c;Cetinic et al, 2012;Hill et al, 2011;Neukermans et al, 2012) and large variability in the environments sampled. Note that in all these studies measurements have been done using red or near-infra-red wavelengths (650 nm < k < 880 nm) to minimize the effect of dissolved substance absorption on the attenuation coefficient, as well as to minimize the effect of particulate absorption on the scattering coefficient.…”
Section: Commercial Technology To Measure Optical Properties In-situmentioning
confidence: 99%
See 3 more Smart Citations
“…The variability in mass specific optical properties, when compared across studies, has been found to be constrained within ±50% despite some variability in the analytical methods used to obtain mass (Boss et al, 2009c;Cetinic et al, 2012;Hill et al, 2011;Neukermans et al, 2012) and large variability in the environments sampled. Note that in all these studies measurements have been done using red or near-infra-red wavelengths (650 nm < k < 880 nm) to minimize the effect of dissolved substance absorption on the attenuation coefficient, as well as to minimize the effect of particulate absorption on the scattering coefficient.…”
Section: Commercial Technology To Measure Optical Properties In-situmentioning
confidence: 99%
“…Remote sensing requirements and the need to understand coastal and near bottom processes, stimulated the development of PM/POC -backscattering proxies (Boss et al, 2009c;Cetinic et al, 2012;Neukermans et al, 2012;Stramski et al, 1999). The availability of relatively cheap and large-depth capable side-scattering (turbidity) sensors encouraged studies relating side-scattering and POC or PM (Baker et al, 2001;Bishop and Wood, 2008;Boss et al, 2009c;Bishop et al, 2012;Cetinic et al, 2012).…”
Section: Commercial Technology To Measure Optical Properties In-situmentioning
confidence: 99%
See 2 more Smart Citations
“…This Wetlabs ECO-BB2FL sensor measures light backscattering at 117˝at the fixed wavelength of 700 nm (β 117 (700) in sr´1¨m´1) as well as chlorophyll fluorescence at a sample rate of 15 minutes (Figure 2). The measured β 117 (700) data (in sr´1¨m´1) was converted into the particulate backscattering coefficient (b bp (700), in m´1) which is a robust proxy of the SPM concentration [8, 29,31]. The b bp (700) coefficient was obtained through the formula b bp (700) = 2πˆ1.1ˆβ p117 (700) [29], with β p117 (700) = β 117 (700) -β w117 (700)~β 117 (700), as the water light backscaterring (β w117 (700)~10´5) is negligible compared to particulate light backscattering signal (β p117 (700)~10´2) in turbid waters.…”
Section: Autonomous Field Measurementsmentioning
confidence: 99%